Avaliação dos impactos de rejeitos de mineração sobre a comunidade perifítica da Bacia do Rio Doce - Franciele de Carvalho Gonçalves (2022)
The collapse of the Fundão dam impacted some rivers in the Doce river hydrographic basin. Periphytic communities are important because they are the base of trophic chains in rivers and they can also be used for bioindication. Our objective was to analyze the structure of these communities in order to verify if there are differences in their composition according to a gradient of impact by tailings from Fundão dam. Water samples (for physical, chemical and metal analyses) and periphytic communities were obtained every six months, between November 2017 and June 2019, at three sites: Carmo river (reference, non-impacted), Gualaxo do Norte river (highly impacted) and Doce river (intermediate impact). We also used the database produced by a monitoring carried out in the region by the IGAM (Minas Gerais Water Management Institute) to compare its results with those obtained in our analyses. the analyses showed that Gualaxo do Norte river was specially different from the others sampled sites. Results suggest that many differences were related to a nutritional and chemical deficiency, since this river was characterized by the lowest concentrations of both nutrients and metals. The results of this study and also those obtained by IGAM showed that all the elements evaluated were below the values established by legislation, except Al and Mn. Thus, the commonly observed lower biomass and richness of the periphytic community in the most impacted site indicated that the tailings wave may have impacted the structure of the communities in a different way than we supposed in the beginning of our study. Furthermore, there were significant differences in the composition of periphytic communities between the rivers studied, with the Gualaxo do Norte river being predominantly composed by Achnanthidium minutissimum, reported as tolerant to extreme conditions. It was evidenced by this study that the periphytic communities are interesting bioindicators that can complement the role of other variables that are traditionally used in the monitoring of aquatic systems.